Applicant Perceptions Regarding the 2020 to 2021 Virtual Ophthalmology Residency Interview and Match Season - Shah, Saumya M.; Barkmeier, Andrew J.; Dalvin, Lauren A.; Tooley, Andrea A. (Journal of Academic Ophthalmology, 2021)
Background The coronavirus disease 2019 pandemic has significantly impacted medical education, notably the mandate for all residency programs to implement virtual (rather than in-person) residency interviews. Understanding residency applicants' perceptions and approach to this novel virtual interview season will be beneficial as potential future interview formats are considered.Objective The aim of this study was to examine perceptions of the 2020 to 2021 ophthalmology residency match applicants regarding the virtual interview season prior to the start of the interview season.Patients and Methods Ophthalmology residency applicants during the 2020 to 2021 cycle were invited to complete the survey between October 20 and 29, 2020. Respondent demographic information, perceived importance of various application details in a normal versus virtual interview season, strengths and limitations of virtual interviews, and preferences for optimal virtual interview format were obtained.Results There were 337 survey respondents, with at least 50% of the survey completed by 190 applicants (56%). Of these, 73% of respondents applied to more than 60 ophthalmology residency programs, and 78% felt that the evaluation of candidates would be impacted by the virtual interview format. Regardless of interview format, United States Medical Licensing Examination Step 1 score and letters of recommendation were perceived to be the two most important factors related to matching at an applicant's top ranked programs. The primary limitation of a virtual interview season was the inability to experience a program's culture in person, while largest strength was cost savings.Conclusion The ophthalmology residency match is a competitive process made potentially more complex by a novel virtual interview format. A detailed postcycle analysis will be important to optimize future interview seasons.
Keywords: virtual interviews; COVID-19; residency; medical education; interviews; residency application; ophthalmology